2022
DOI: 10.1093/mnras/stac534
|View full text |Cite
|
Sign up to set email alerts
|

New low mass ratio contact binaries in the Catalina Sky Survey

Abstract: We present the identification and photometric analysis of 30 new low mass ratio (LMR) totally eclipsing contact binaries found in Catalina Sky Survey data. The LMR candidates are identified using Fourier coefficients and visual inspection. We perform a detailed scan in the parameter plane of mass-ratio (q) versus inclination (i) using Phoebe-0.31 scripter to derive the best (q, i) pair for the initial models. The relative physical parameters are determined from the final model of each system. A Monte Carlo app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 160 publications
6
54
0
Order By: Relevance
“…According to the photometric solutions, we knew that the fill-out factors of eleven targets are between 18.9% and 94.3%, which showed that our contact binaries have shallow, medium and deep contact systems. Therefore, it proved the conclusion proposed by Christopoulou et al (2022). Table 9 listed the physical parameters obtained by us and those determined by Sun et al (2020).…”
Section: Discusstions and Conclusionsupporting
confidence: 76%
See 1 more Smart Citation
“…According to the photometric solutions, we knew that the fill-out factors of eleven targets are between 18.9% and 94.3%, which showed that our contact binaries have shallow, medium and deep contact systems. Therefore, it proved the conclusion proposed by Christopoulou et al (2022). Table 9 listed the physical parameters obtained by us and those determined by Sun et al (2020).…”
Section: Discusstions and Conclusionsupporting
confidence: 76%
“…Among the eleven systems, J164000 has the largest temperature difference between the two components, which is 563K. Christopoulou et al (2022) proposed a conclusion that contact binaries with low-mass ratios can present deep or medium or shallow degree of contact. Qian et al (2005a) defined that the contact binaries whose degree of contact exceeds 50% as deep contact binaries.We defined medium and shallow contact configuration as that the fill-out factors are between 25% and 50%, and less than 25%.…”
Section: Discusstions and Conclusionmentioning
confidence: 99%
“…These include semimajor axis-period relations (Şenavcı et al 2016), total mass-period relations (Dimitrov & Kjurkchieva 2015), main-sequence approximation of the massive components, mass-luminosity relations (Sun et al 2020;Ren et al 2021), period-mass ratio relations (Schuh et al 2009), etc. We adopted the empirical luminosity-mass relation for the primary mass from Christopoulou et al (2022):…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of survey photometry in the detection of interesting, particularly low mass ratio contact binary systems has received considerable attention recently (Christopoulou et al 2022;Devarapalli et al 2020;Wadhwa et al 2022b Her (Caton et al 2019). In both cases, the survey analysis over-estimated the mass ratio compared to spectroscopic mass ratio in the case of CN Hyi and dedicated ground-based observations in the case of V1187 Her.…”
Section: Discussionmentioning
confidence: 99%
“…Lucy (1968) suggested that the discrepancy in the brightness and size of the secondaries was due to the transfer of energy from the primary to the secondary within the common envelope. A number of authors have explored the relationship between the mass ratio and luminosity and the transfer of energy between the components (Csizmadia & Klagyivik 2004;Wang 1994) with general agreement that energy transfer is a function of both the mass ratio and luminosity ratio.…”
Section: Energy Transfer and Densitymentioning
confidence: 99%